IMPACT OF INFORMATION SYSTEMS IN THE SUPPLY CHAIN: A SYSTEMATIC LITERATURE REVIEW - Hattar, Issa Zayed; Felföldi, János (Applied Studies in Agribusiness and Commerce, 2024)
Information system (IS) has in many ways impacted supply chain management (SCM), from accumulating. organizing, and assessing data to optimizing the whole operation. With the help of technological advancement and efficient data control, companies can move forward with amending the SCM according to what customers expect. The present study has predominantly focused on how the IS helps the managers and the entire workforce to give their best effort to make SCM successful which accordingly can control the productivity, revenue and data throughout business operations. This systematic literature review is based on an analysis of over 250 articles published in peer-reviewed journals over the last four years to reach out to the learning areas aligned with the topic of how IS aids SCM in different sectors. In general, the findings point out that the integration of information technology into their supply chains provides a competitive advantage. In addition, the study indicates that technology enhances supply chain management’s information accessibility, insight, agility, cooperation, and client loyalty. On the other hand, software’s could improve supply chain efficiency, but using new technology comes with risk. Unwilling partners and suppliers, poor planning and preparation, communication difficulties, customer issues, complaints, and awkward encounters are among the common complications.